Studies on the Use of some Weedicides on Lantana camara - Sinha, B. N. (Indian Forester, 1976)
Lantana camara, a woody shrub, is an obnoxious weed that has been gradually invading the forests and ousting valuable timber species. Open forest and blanks are particularly vulnerable. Apart from impeding natural regeneration of trees in forests, this tenacious weed has been posing a big problem in plantation areas. Even though the area is cleared or Lantana and burned before raising plantations, this species immediately comes up again. In Bihar, weeding is done in plantations for the first three years, scraping a metre round the planted seeding, and hoeing is done within a radius or O.5 m. The average cost of weeding and hoeing in Lantana free areas is Rs. 150/- per ha per year, whereas in Lantana infested areas it is higher than this. The cost or site clearance in Lantana infested areas is not less than Rs. 100/- per ha. Where Lantana occurs, It persists is the gaps and amothers the plantation soon after weeding is stopped. Even if the planted species continues to exist, it has to struggle desperately for its existence. Ramaswamy and Gowda (1959) reported that there was a possibilites of eradicating Lantuna camara with weedicides like spontox, but an economical dose had to be found out. Although it is not proper to equate killing out with cutting back, and, cousequently, to equate the cost of effective application of weedicides with the cost or weedings during the first few years, the comparison gives an idea of the economies involved. In an effort to find out a cheap and effective treatment to erradicate Lantana, the use of some weedicides was studied in Latehar Division (Bihar State) and the results or those studies are preseated here.